A 4 Week Core Stability Exercise Programme Using Swiss Ball, Theraband and Floor Exercises in Cricketers with Low Back Pain: a Randomised Clinical Trail - Arati Mahishale; Varun Naik; Basavaraj Motimath (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Introduction Low back pain (LBP) is one of the most common complaints seen in primary care, with 60-85% of adults experiencingit at some time in their lives. Current studies have done to see the effect of core strengthening exercises using Swiss ball, theraband and floor exercises in general population with low back pain, but there are no studies which have compared the effectiveness of Swiss ball, theraband and floor exercises in core strengthening in cricketers with low back pain. Objective To study and compare the effectiveness of Swiss ball exercises, theraband exercises and floor exercises in cricketers with low back ache in terms of pain and back strength. Study design Randomized Clinical Trial Methods Sixty competitive cricket players between the ages 18 to 35 years were randomly assigned to 1 of 3 groups. Group A –Swiss Ball Exercises (n=20), Group B - Theraband Exercises (n=20) and Group C - Floor exercises (n=20). Baseline pain and back strength was taken pretreatment i.e. 1st day and post treatment i.e. 4th week. VAS was used to assess pain and Pressure Bio feedback was used to measure the back strength in cricketers with low back ache. Comparison of data within group and between groups of the pre and post values was done. Results The results revealed that within group analysis in all the three groups showed statistically significant improvement in terms of pain and back strength (p<0.001). Whereas when between groups was analyzed, Group B (theraband) showed significant improvement when compared to Group A (Swiss ball) and Group C (floor) showed significant improvement when compared to Group C. Conclusion Although the study showed beneficial results in all the 3 groups, but the results reflected that theraband group had better improvement than the other two groups which was measured in terms of strength improvement and pain reduction.